Effects of a postweld heat treatment on a submerged arc welded ASTM A537 pressure vessel steel - de Brito, VLO; Voorwald, HJC; das Neves, N.; Bott, I. D. (Asm International, 2001)
Postweld heat treatment (PWHT) is frequently applied to steel pressure vessels, following the requirements of the ASME code (section VIII), which establishes the parameters of the PWHT based on the thickness and chemical composition of the welded section. This work shows the results of an analysis undertaken on a sample of ASTM A537 C1 steel subjected to qualifying welding procedure tests including PWHT (650 degreesC/5 h), the results obtained showed that this PWHT practice promoted a reduction in the mechanical properties of the base metal and the heat-affected zone (HAZ).
Keywords: microalloyed steels; postweld heat treatment; pressure vessels; submerged arc welding